2003
DOI: 10.1103/physrevb.68.024514
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of coherent effects in the conductivity of superconductor/insulator/normal-metal/insulator/superconductor junctions

Abstract: An experimental and theoretical study is presented of coherent effects in electron transport in the doublebarrier SINIS junctions ͑where S, I, and N denote a superconductor, insulator, and normal metal, respectively͒. The appearance of a steplike subgap structure in the current-voltage characteristics of the Nb/Al/AlO x /Al/AlO x /Al/Nb superconducting junctions at a voltage Vϳ⌬ Nb /e ͑where ⌬ Nb is the superconducting energy gap of Nb͒ is interpreted as a manifestation of a nonequilibrium supercurrent at fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This is especially true in the case of the hole-doped cuprates. We note that not only are π-junctions readily obtained with Nb, Al and their oxides, 51 but the associated zero-bias conductance peaks and higher harmonic order Josephson phase relations in such conventional junctions have also been observed, 51,52,53,54,55,56 as in YBCO. 57,58 V. SUMMARY…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true in the case of the hole-doped cuprates. We note that not only are π-junctions readily obtained with Nb, Al and their oxides, 51 but the associated zero-bias conductance peaks and higher harmonic order Josephson phase relations in such conventional junctions have also been observed, 51,52,53,54,55,56 as in YBCO. 57,58 V. SUMMARY…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, from the results we obtained with these two FS's, it is evident that the results obtained from such devices, the grain boundaries of which have not been analyzed with atomic scale precision as was done with the Bi2212 c-axis twist experiments, 4 might also have a more conventional explanation. 51,52,53,54,55,56 It has been suggested that the experimental I c (θ) observed in (001) tilt grain boundary junctions can only be understood in terms of interface defects, regardless of the OP. 42 Of course, in Bi2212, it has long been established that a significant amount of static defects exist not only on the top cleaved surface, 43 but throughout even the best single crystals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Multiple Andreev reflection ͑MAR͒ features [22][23][24] have been observed in the current-voltage characteristics of nanojunctions with superconducting leads. 25 Recently an experimental observation of ABS levels was reported 10,[18][19][20][21] in double barrier SISЈIS junctions.…”
Section: Introductionmentioning
confidence: 99%
“…10,[16][17][18][19][20][21] Up to now the quantized states ͑re-ferred also as to Andreev bound states or ABSs͒ were experimentally observed in only a few systems. Scanning tunneling spectroscopy measurements provide evidence for ABS levels in ͑i͒ the normal core of an Abrikosov vortex 16 and ͑ii͒ normal wires embedded in a superconducting matrix.…”
Section: Introductionmentioning
confidence: 99%